POLA PERTUMBUHAN DAN SENSITIVITAS ANTIBIOTIK BAKTERI PENYEBAB INFEKSI NOSOKOMIAL DI RUANG ICU RUMAH SAKIT - Mudrika Mudrika; Misnarliah Misnarliah (Nursing Arts, 2022)
The prevalence of nosocomial infection in hospitals in Makassar is still quite high. Along with this, there is the problem of bacterial resistance to several classes of antibiotics called multidrug resistance organisms (MDROs). The results of previous studies reported that the prevalence of MDROs in Indonesia continued to increase from 2013, and the unit with the highest incidence of MDROs compared to other units was the Intensive Care Unit (ICU). This study aims to determine the growth patterns of bacteria and their sensitivity to antibiotics as well as sources of transmission that have the potential to cause nosocomial infections in the ICU room at Hikmah Hospital Makassar, as an effort to limit/terminate the transmission of bacteria that cause nosocomial infections in hospitals. This research is a descriptive research using laboratory observational methods. The research sample was in the form of swab/swab specimens obtained from the ICU room of Hikmah Makassar Hospital which consisted of swabs from the patient's hands, noses of health workers, equipment, floors, walls, room mobilers and room air. The stages of specimen examination include isolation, culture, purification, identification and antibiotic sensitivity testing which were carried out at the Immunology and Molecular Microbiology Laboratory, Hasanuddin University. The results showed that there were 2 types of pathogenic bacterial species that were successfully isolated and identified from all specimen samples, namely Staphylococcus aureus (4 isolates), each of which came from a specimen; patient swabs, equipment, room air mobilizer, and E.Colii (1 isolate) originating from floor swab specimens. The results of the antibiotic sensitivity test of the 4 S. aureus isolates showed that 3 isolates were resistant to Ceftadizime, 2 isolates were resistant to Tetracycline, and 4 isolates were still sensitive to the antibiotics Ciprofloxacin, Cefotaxim, Ceftriaxone and Imipenem. And the results of the antibiotic sensitivity test for E. colii isolates showed results that were sensitive to Ciprofloxacin, Cefotaxim, Ceftriaxone, Tetraxyclin, and Imipenem. However, it is resistant to Ceftadizime. Based on the results of this study it can be concluded that the growth pattern of pathogenic bacteria that have the potential to cause nosocomial infections in the ICU room of Rs. Hikmah Makassar is Staphylococcus aureus with 90%, followed by E. coli 10%. And the sources of transmission that have the most potential to cause nosocomial infections in the ICU are room mobiles, equipment, floors, patients and room air.